Identification of genetic polymorphisms in MC4R and GPX5 genes in the autochthonous Greek black pig breed - Karatosidi, D; Avgeris, E; Michailidis, G (Journal of the Hellenic Veterinary Medical Society, 2024)
The importance of local breeds as genetic reservoirs of valuable genetic variation is well established and the evaluation of the genetic structure of autochthonous pig breeds is very important for conservation of local pig breeds and preservation of diversity. Although local farm animal breeds are important for the maintenance of genetic diversity, most of them are now in danger of extinction. The autochthonous Greek black pig breed, which was raised locally and is well known for the high quality of its meat, is the only traditional indigenous pig breed reared in Greece and is able to adapt to different and harsh environmental conditions. Recent studies have reported that gene polymorphisms in melanocortin 4 receptor (MC4R) and glutathione peroxidase 5 (GPX5) genes are associated with litter size in pig and can be used as genetic markers in gene assisted selection programs for the improvement of reproductive performance. The objective of this study was to investigate the existence of these polymorphisms in the autochthonous Greek black pig breed. One hundred sixty pigs raised in Greece were included in the study. DNA was extracted and genotyping was performed using RFLP - PCR. The molecular results revealed that for MC4R, genotype GG had a frequency of 0.37, GA 0.44 and AA 0.19, while the frequency of allele G was 0.56 and of A 0.44. For GPX5, genotype AA had a frequency of 0.19, AB 0.41 and BB 0.40, with frequencies of alleles A and B being 0.43 and 0.57, respectively. These data revealed that all genotypes of the two genes were present in the investigated population, indicating that these genes could be used for Marker-assisted selection programmes for the genetic improvement of reproductive characteristics of this breed.